Initial Literacy: Pedagogical Decisions and Definitions of a Teacher to Promote Oral and Written Language in an Indigenous Preschool - Delgado-Gastélum, Glenda (2023)
Objective. This article aims to describe the initial literacy processes promoted in an indigenous preschool located in Baja California, Mexico, attended by indigenous children. Methodology. A qualitative study with an ethnographic design was conducted. Participant observation in the classroom and a semi-structured interview with a teacher were carried out in order to deepen the authors’ understanding of the teacher’s decisions in teaching written language. Once collected, the data were transcribed and analyzed using the qualitative content analysis technique (Mayring, 2000). Results. The main findings indicate that the participant prioritized activities for teaching the writing of the proper name. Hence, she granted insufficient reading spaces and brief situations for the use of oral language. In addition, the use of Spanish prevailed in teaching and communication, and the Mixtec indigenous language was used for ritual and cultural purposes. In general, the activities for teaching written language implemented by the participant were based on her interpretation of the official program of studies. Conclusions. The teacher’s inclination to teach conventions of reading and writing words was observed. The teaching activities unevenly provoked the learning of the written language among the students. In addition, she used Spanish as the language of instruction and did not incorporate the indigenous language regularly. The teacher’s teaching decisions are related to the enrollment of her group, the academic performance detected, the linguistic diversity present, and the demands of the school curriculum.